Adopting a Constraints-Led Approach to Enhance Skill Acquisition for Fast Bowlers in Grassroots Cricket - Mikael Jamil; Lewis Woolston; Simon Manthorpe; Saumya Mehta; Daniel Memmert; Allistair McRobert (FoundAE, 2023)
In this quantitative study, a bespoke coaching drill was designed and tested over a 16-week period with the ultimate aim of improving the bowling accuracy of 6 participant seam bowlers. This experiment consisted of 6 participants that were all male and had a mean age of 19.5 ± 7.5, mean height (cm) of 184.75 ± 5.57 and mean weight (kg) of 78.05 ± 9.87. Due to the repeated measures experimental design, paired samples t-tests were conducted to assess the effectiveness of this coaching intervention and compare performances between the "control" phase and the "training" phase. Results revealed that this purposely designed coaching drill led to a significant improvement of bowling lines (p 0.001) with a moderate effect size and bowling lengths (p 0.001) with a large effect size. This coaching intervention did not however have any significant effect upon bowling discipline (p = 0.134).  Evidence is discovered proving that the regular repetition of exercises over a prolonged period of time can ultimately enhance motor skill refinement. From a practical perspective, coaches can replicate the drill introduced in this study as a means of skill acquisition and skill refinement for their seam bowlers.